PENGGUNAAN SAPAAN MASYARAKAT TUTUR DALAM BAHASA SUMBA DIALEK KAMBERA DI DESA LAIPANDAK, KECAMATAN WULLA WAIJILU, KABUPATEN SUMBA TIMUR, NUSA TENGGARA TIMUR - Mince Babang Noti; Umi Hartati (CARAKA, 2019)
The purpose of this research is to describe (1) types of greetings, (2) greeting functions, and (3) factors that influence the use of greetings in the Sumba language of dialect Kambera in Laipandak Village, Wulla Waijilu District, East Sumba Regency, East Nusa Tenggara. The type of this research is qualitative descriptive. The data collection technique uses the method of listening with basic tapping techniques along with advanced techniques, namely the skillful listening technique (SLC), namely skillful listening techniques (SLC), recording techniques, and note-taking techniques; and proficient methods with basic fishing techniques accompanied by advanced techniques, namely leading skill techniques. The data analysis technique uses the translational equivalent method with the basis of the determinant elements (PUP) accompanied by advanced techniques, namely the comparative connection technique equates the main thing (HBSP). Presentation of the results of data analysis using formal and informal methods. The results of this study indicate that (1) types of greetings consist of (a) pronouns, (b) self-names, (c) greetings of kinship terms, (d) the title of 'noble' Maramba, or 'servant', and profession, (e)Â  a deixis or pointer greetings, and (f) a zero characteristic; (2) the greeting function consists of calls, arrangements for speech turn, rituals and social contexts, requires and reduces threats; and (3) factors that influence the use of greetings consist of age, gender, situation, social status, kinship relationships, and intimacy relationships.